Creative perception and language learning strategies among Malaysian Form Four students - Ananda Kumar Palaniappan; Sathiadevi Kanagasabai (Journal of Modern Languages)
Many factors have been reported to affect language learning and language achievement. Among them are cognitive constructs like intelligence and creativity (Pabniappan, I996b). Perceptions, attitudes and motivation, too, are found to influence second language acquisition. However, few studies have investigated the relationship between creative perception i.e. perception of oneself as creative, and language learning strategies. This paper intends to (a) provide empirical evidence on the nature of the relationship between the two dimensions of creative perception and language learning strategies used by second language learners. And (b) to find out if there any differences in the relationships between the two dimensions in terms of gender, type of school and socio-economic status.